2022
DOI: 10.1111/1365-2656.13655
|View full text |Cite
|
Sign up to set email alerts
|

Tropical forest dung beetle–mammal dung interaction networks remain similar across an environmental disturbance gradient

Abstract: 1. Conservation outcomes could be greatly enhanced if strategies addressing anthropogenic land-use change considered the impacts of these changes on entire communities as well as on individual species. Examining how species interactions change across gradients of habitat disturbance allows us to predict the cascading consequences of species extinctions and the response of ecological networks to environmental change.2. We conducted the first detailed study of changes in a commensalist network of mammals and dun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Furthermore, in the German temperate forest, we see less overlap in dung beetle diets than would be expected by random dung choice, under the expectation that dung beetles are generalist dung consumers ( Hanski & Cambefort, 1991 ; Nichols et al, 2009 ; Frank et al, 2018a ). Rodents were more dominant in the German mammal dung–dung beetle network than expected based on previous conclusions from the research of mammal dung–dung beetle networks ( Hanski & Cambefort, 1991 ; Nichols et al, 2008 ; Frank et al, 2018a ; Raine & Slade, 2019 ; Chiew et al, 2022 ). Previous research suggested that German networks are dominated by wild boar and deer, among other medium and large-bodied mammals, while rodents were mostly missing.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Furthermore, in the German temperate forest, we see less overlap in dung beetle diets than would be expected by random dung choice, under the expectation that dung beetles are generalist dung consumers ( Hanski & Cambefort, 1991 ; Nichols et al, 2009 ; Frank et al, 2018a ). Rodents were more dominant in the German mammal dung–dung beetle network than expected based on previous conclusions from the research of mammal dung–dung beetle networks ( Hanski & Cambefort, 1991 ; Nichols et al, 2008 ; Frank et al, 2018a ; Raine & Slade, 2019 ; Chiew et al, 2022 ). Previous research suggested that German networks are dominated by wild boar and deer, among other medium and large-bodied mammals, while rodents were mostly missing.…”
Section: Discussionmentioning
confidence: 54%
“…For instance, there are some direct feeding observations at dung piles, but this is likely biased towards larger, more obvious dung, such as that from elephants, cows, and humans ( Young, 1981 ; Hanski & Cambefort, 1991 ; Scholtz, Davis & Kryger, 2009 ). Further, experimentally deployed dung often represents common or readily available species, even using non-native species from zoos ( Hanski & Cambefort, 1991 ; Frank et al, 2018a ; Raine & Slade, 2019 ; Chiew et al, 2022 ). Overall, this has often led to the assumption that dung beetles primarily consume dung from large- and medium-sized mammals ( Hanski & Cambefort, 1991 ; Scholtz, Davis & Kryger, 2009 ; Simmons & Ridsdill-Smith, 2011 ; Bogoni & Hernández, 2014 ; Frank et al, 2018a ; Frank et al, 2018b ; Raine et al, 2018 ; Raine & Slade, 2019 ; Bogoni, Da Silva & Peres, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pitfall traps baited with fecal material clearly remain a valid, useful, and efficient tool for dung beetle surveys, providing reliable capture success for species that feed on feces. Their use in biodiversity surveys and ecological studies has been increasing over the past 30 years (Raine & Slade, 2019 ), many of which focus on dung beetle assemblage metrics (Bogoni et al, 2019 ; Chiew et al, 2021 ; Enari et al, 2018 ; Fuzessy et al, 2021 ; Nependa et al, 2021 ), and dung beetle‐mammal interaction networks (Nichols et al, 2009 ; Raine et al, 2018 ). Clearly, it is not our intention to reject a widely established and broadly accepted sampling protocol for the dung beetle field studies.…”
Section: Discussionmentioning
confidence: 99%
“…Without sufficient providers of this habitat, the abundance and richness of dung beetles will be low (Buse et al., 2021). Dung beetle species richness is positively correlated with mammal biomass (Culot et al., 2013), and high diversity of native mammals enhances the resilience of dung beetle–mammal networks (Chiew et al., 2022), leading to increased abundance, richness and diversity of dung beetles (Amézquita & Favila, 2010; Buse et al., 2021; Nependa et al., 2021). Additionally, the abundance of dung beetles may be related to native burrowing mammals (Lindtner et al., 2019) due to their effects on soil structure and interspecies facilitative or commensal relationships.…”
Section: Restoration Triangle For Dung Beetlesmentioning
confidence: 99%